MANAJEMEN MASJID SEKOLAH SEBAGAI LABORATORIUM PENDIDIKAN KARAKTER BAGI PESERTA DIDIK - Muhammad Najib; Novan Ardy Wiyani; Sholichin S (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
This study is a qualitative study. The objective of this study was to find out the managerial activity which was done by Biah section to use school mosque as character education laboratory for students at SMP Al-Irsyad Al-Islamiyyah Purwokerto Center Java. The interview, observation, and documentation were used to collect the data. The data were analyzed by general inductive approach. Based on the result of the study it was found that there were four activities that were done by Biah section to use school mosque as character education laboratory for students. The first is to plan the school mosque activity as character education laboratory. The second is to organize the school mosque activity as character education laboratory. The third is to implement the school mosque activity as character education laboratory, and the last is to evaluate the school mosque activity as character education laboratory.